Positive electrode material and battery

By adjusting the conductivity and particle size distribution of the lithium nickel-cobaltate composite oxide in the positive electrode material, combined with doping elements, the problem of structural stability reduction caused by the increase of nickel content is solved, and a positive electrode with high capacity and cyclic stability is achieved Material.

CN119133430APending Publication Date: 2024-12-13SHENZHEN CITY BATTERY NANOMETER TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411203424.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing positive electrode materials have challenges in improving energy density and cycle stability, especially due to the reduction in structural stability caused by the increase in nickel content and the problems of lithium-nickel mixed discharge, and the existing improvement effect is limited.

Method used

Using lithium nickel-cobaltate-based composite oxide as the positive electrode material, the relationship between powder conductivity, particle size distribution width and crystal plane half-maximum width is controlled to control (δ*span)/FWHM within the range of 0.001≤0.5, combined with doping Miscellaneous elements such as Ti, Sb, Ta, Nb, W, Zr, Sr, etc. regulate particle size and chemical formulas, and improve lithium ion transmission efficiency and electron conduction ability.

Benefits of technology

The cathode material with high capacity, strong structural stability and cyclic stability has been achieved. By balancing the grain size and grain boundary number, lithium ion transmission efficiency and electron conduction capability are improved, discharge capacity is improved, and structural stability and cyclicity are solved. Performance issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133430A_ABST
    Figure CN119133430A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material and a battery, the positive electrode material is a lithium nickel cobalt oxide composite oxide, the powder conductivity of the positive electrode material is delta S / cm < 2 >, the particle size distribution width of the positive electrode material is Span, in an XRD pattern of the positive electrode material, the half-peak width of a characteristic peak corresponding to a (003) crystal plane of the positive electrode material is FWHM, and the positive electrode material meets the condition that (delta * span) / FWHM is more than 0.001 and less than or equal to 0.5. The positive electrode material provided by the invention has high capacity, strong structural stability and cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to a positive electrode material and a battery. Background Art

[0002] Lithium-ion batteries are widely used in laptops, mobile phones, digital products and other fields due to their high energy density, good safety performance, long cycle life and environmental friendliness. The development of positive electrode materials is relatively slow compared to the development of large-capacity negative electrode materials (about 800-1000mAh / g). Therefore, researchers currently focus on developing large-capacity and high-voltage positive electrode materials to improve the energy density of lithium-ion batteries.

[0003] Commonly used ternary positive electrode materials show characteristics such as high capacity, high voltage, good cycle life and good safety, and have become the main positive electrode materials for power battery development. In order to improve the energy density and capacity of positive electrode materials, the nickel content is generally increased. However, as the nickel content in the ternary positive electrode material increases, the structural stability of the positive electrode material will deteriorate, resulting in a decrease in cycle performance and deterioration in safety performance. At present, solid phase coating or metal doping is conventionally used to reduce problems such as lithium-nickel mixing and structural degradation, but the improvement effect is still very limited.

[0004] How to comprehensively improve the capacity, cycle stability and rate performance of positive electrode materials is a technical problem that still needs to be solved. Summary of the invention

[0005] The purpose of the present application is to provide a positive electrode material and a battery. The positive electrode material of the present application can have high capacity, strong structural stability and cycle stability.

[0006] In a first aspect, the present application provides a positive electrode material, wherein the positive electrode material is a nickel cobalt lithium oxide composite oxide, and the powder conductivity of the positive electrode material is δS / cm 2 , the particle size distribution width of the positive electrode material is Span, in the XRD spectrum of the positive electrode material, the half-peak width of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material is FWHM, and the positive electrode material satisfies: 0.001<(δ*span) / FWHM≤0.5.

[0007] In some embodiments, the particle size volume distribution width of the positive electrode material satisfies: 0.9≤Span≤1.5.

[0008] In some embodiments, 0.15≤FWHM≤0.19.

[0009] In some embodiments, the powder conductivity of the positive electrode material is δS / cm 2 , 0.005≤δ≤0.08.

[0010] In some embodiments, 0.01<(δ*span) / FWHM≤0.24.

[0011] In some embodiments, the particle size of the positive electrode material satisfies: 1.0 μm<D 10 <7.0μm,8.0μm<D 50 <20.0μm,15μm<D 90 <30μm.

[0012] In some embodiments, the particle strength of the positive electrode material is ≥0.28Mpa.

[0013] In some embodiments, the compaction density of the positive electrode material is ≥2.9 g / cm 3 .

[0014] In some embodiments, the specific surface area of ​​the positive electrode material is 0.3 m 2 / g~0.9m 2 / g.

[0015] In some embodiments, the lithium ion diffusion coefficient of the positive electrode material is greater than 0.001 m 2 / s.

[0016] In some embodiments, the chemical formula of the positive electrode material is Li a Ni x Co y N z M w O2, wherein 0.75≤a≤1.05, 0.80≤x<1, 0<y≤0.10, 0<z≤0.10, 0<w≤1-xyz, N is Mn or Al, and M is a doping element.

[0017] In some embodiments, the M element includes at least one of Ti, Sb, Ta, Nb, W, Zr, Sr, and metal elements of Groups IVB to VIB.

[0018] In some embodiments, the DC resistance of the positive electrode material is less than 0.01Ω.

[0019] In a second aspect, the present application provides a battery, comprising a positive electrode material.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The positive electrode material provided in the present application can control the positive electrode material to meet 0.001<(δ*span) / FWHM≤0.5, wherein FWHM is the half-peak width of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material. The larger the FWHM value, the smaller the grain size, the more the number of grain boundaries between the grains, the lower the lithium ion transmission efficiency in the positive electrode material particles, the lower the capacity of the positive electrode material, but the structural stability of the positive electrode material increases. The smaller the FWHM value, the larger the grain size, the fewer the number of grain boundaries between the grains, the higher the lithium ion transmission efficiency in the positive electrode material particles, and the higher the capacity of the positive electrode material. However, the increased size of the grains will cause the positive electrode material particles to be more easily crushed and broken during the charge and discharge process due to the easier contraction and expansion of the unit cells, and the structural stability of the positive electrode material will decrease. The present application controls 0.001<(δ*span) / FWHM≤0.5, and associates FWHM with the powder conductivity and particle size distribution width of the positive electrode material. By adjusting the particle size distribution width of the positive electrode material, the lithium ion transmission efficiency between the positive electrode material particles is improved, and the energy density of the positive electrode material is improved. At the same time, the powder conductivity is coordinated to improve the electronic conductivity of the positive electrode material, and the discharge capacity of the positive electrode material is comprehensively improved, thereby improving the capacity loss caused by the small grain size. Therefore, when the present application controls the positive electrode material to meet the above requirements, the positive electrode material can have high capacity, strong structural stability and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0023] Figure 1 A schematic diagram of a process for preparing a positive electrode material provided in an embodiment of the present application.

[0024] Figure 2a This is an electron microscope image of the positive electrode material prepared in Example 1 of the present application.

[0025] Figure 2b This is an electron microscope image of the positive electrode material prepared in Comparative Example 1 of the present application.

[0026] Figure 3 This is a comparison chart of the cycle performance of the positive electrode materials prepared in Example 1 of the present application and Comparative Example 1.

[0027] Figure 4 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application. DETAILED DESCRIPTION

[0028] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.

[0029] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0031] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs.

[0032] As used herein, the term "matrix" refers to a lithium-based composite oxide synthesized by mixing a precursor with a lithium salt through a high-temperature solid-phase reaction, and includes lithium and metal elements.

[0033] The present application provides a positive electrode material, which is a nickel-cobalt-lithium oxide composite oxide. The powder conductivity of the positive electrode material is δS / cm 2 , the particle size distribution width of the positive electrode material is Span, in the XRD spectrum of the positive electrode material, the half-peak width of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material is FWHM, and the positive electrode material satisfies: 0.001<(δ*span) / FWHM≤0.5.

[0034] The positive electrode material provided in the present application can control the positive electrode material to meet 0.001<(δ*span) / FWHM≤0.5, wherein FWHM is the half-peak width of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material. The larger the FWHM value, the smaller the grain size, the more the number of grain boundaries between the grains, the lower the lithium ion transmission efficiency in the positive electrode material particles, the lower the capacity of the positive electrode material, but the structural stability of the positive electrode material increases. The smaller the FWHM value, the larger the grain size, the fewer the number of grain boundaries between the grains, the higher the lithium ion transmission efficiency in the positive electrode material particles, and the higher the capacity of the positive electrode material. However, the increased size of the grains will cause the positive electrode material particles to be more easily crushed and broken during the charge and discharge process due to the easier contraction and expansion of the unit cells, and the structural stability of the positive electrode material will decrease. The present application controls 0.001<(δ*span) / FWHM≤0.5, and associates FWHM with the powder conductivity and particle size distribution width of the positive electrode material. By adjusting the particle size distribution width of the positive electrode material, the lithium ion transmission efficiency between the positive electrode material particles is improved, and the energy density of the positive electrode material is improved. At the same time, the powder conductivity is coordinated to improve the electronic conductivity of the positive electrode material, and the discharge capacity of the positive electrode material is comprehensively improved, thereby improving the capacity loss caused by the small grain size. Therefore, when the present application controls the positive electrode material to meet the above requirements, the positive electrode material can have high capacity, strong structural stability and cycle stability.

[0035] In some embodiments, the particle size volume distribution width of the positive electrode material satisfies: 0.9≤Span≤1.5, which can be 0.9, 1.0, 1.1, 1.2, 1.3, 1.35, 1.4, 1.45 or 1.5, etc., and of course, it can be other values ​​within the above range, which are not limited here. It should be noted that the particle size volume distribution width of the positive electrode material here is measured based on all particles. Specifically, the particle size volume distribution curve of the positive electrode material particles is measured by the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Co., Ltd. of the United Kingdom with reference to the determination method of GB / T 19077-2016, and the Span value = (D 90 -D 10 ) / D 50 .

[0036] In some embodiments, in the XRD spectrum of the positive electrode material, the half-peak width of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material is FWHM, 0.15≤FWHM≤0.19. Specifically, FWHM can be 0.15, 0.16, 0.165, 0.17, 0.175, 0.18, 0.185 or 0.19, etc., and of course it can also be other values ​​within the above range, which are not limited here. When the FWHM value is too large, the smaller the grain size of the positive electrode material, the more the number of grain boundaries between the grains, the lower the lithium ion transmission efficiency in the positive electrode material particles, and the lower the capacity of the positive electrode material. The smaller the FWHM value, the larger the grain size, the smaller the number of grain boundaries between the grains, the higher the lithium ion transmission efficiency in the positive electrode material particles, and the higher the capacity of the positive electrode material. However, the increased size of the grains will cause the positive electrode material particles to be more easily crushed and broken during the charge and discharge process, and the structural stability of the positive electrode material will decrease, which is not conducive to the improvement of the cycle performance.

[0037] In some embodiments, the powder conductivity of the positive electrode material is δS / cm 2 , 0.005≤δ≤0.08, specifically 0.005S / cm 2 , 0.008S / cm 2 , 0.01S / cm 2 , 0.02S / cm 2 , 0.03S / cm 2 , 0.04S / cm 2 , 0.05S / cm 2 , 0.06S / cm 2 , 0.07S / cm 2 or 0.08S / cm 2 Of course, it can also be other values ​​within the above range and is not limited here.

[0038] In some embodiments, 0.01<(δ*span) / FWHM≤0.24, when (δ*span) / FWHM is within this range, the high capacity and strong cycle stability of the positive electrode material are more prominent. This may be because the three parameters reach the best balance state, and the capacity loss caused by small grains can be effectively compensated by the synergistic effect of conductivity and particle size distribution width, so that the electrochemical performance of the positive electrode material reaches a better state.

[0039] In some embodiments, the particle size of the positive electrode material satisfies: 1.0 μm<D 10 <7.0μm.D 10Specifically, it can be 1.1μm, 1.2μm, 1.5μm, 2.0μm, 2.5μm, 2.8μm, 4.5μm, 4.9μm, 5.2μm, 5.5μm, 6.0μm or 6.99μm, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0040] In some embodiments, the particle size volume distribution of the positive electrode material satisfies: 8.0 μm < D 50 <20.0μm.D 50 Specifically, it may be 8.1 μm, 8.5 μm, 9.0 μm, 9.5 μm, 10.0 μm, 12.5 μm, 15 μm, 18.5 μm or 19.9 μm, etc. Of course, it may also be other values ​​within the above range, which is not limited here.

[0041] In some embodiments, the particle size volume distribution of the positive electrode material satisfies: 15 μm < D 90 <30μm, D 90 Specifically, it may be 15.1 μm, 15.2 μm, 15.5 μm, 18 μm, 20.5 μm, 22.5 μm, 25 μm, 28.5 μm or 29.9 μm, etc. Of course, it may also be other values ​​within the above range, which is not limited here.

[0042] When the particle size of the positive electrode material is controlled within the above range, especially the smaller D10 and the larger D90, it means that the positive electrode material has a wider particle size volume distribution, which is beneficial to improve the gram capacity of the positive electrode material. It should be noted that the positive electrode material here is measured based on all particles.

[0043] In some embodiments, the positive electrode material has the general chemical formula Li a Ni x Co y N z M w O2, wherein 0.75≤a≤1.05, 0.80≤x<1, 0<y≤0.10, 0<z≤0.10, 0<w≤1-xyz, N is Mn or Al, and M is a doping element.

[0044] Specifically, the value of a can be 0.75, 0.79, 0.82, 0.89, 0.92, 0.95, 0.99, 1.0, 1.01, 1.02 or 1.05, etc. It can be understood that when the molar content of Li in the positive electrode material is small, Ni easily enters the Li layer, and the cation mixing is obvious, resulting in poor stability of the electrochemical cycle. When the molar content of Li in the positive electrode material is large, excess residual alkali will form on the surface of the material, increasing the irreversible capacity loss and deteriorating the cycle performance. Preferably, the value of a is 0.95 to 1.05.

[0045] The value of x can be 0.8, 0.82, 0.83, 0.85, 0.89, 0.9, 0.92, 0.95, 0.98 or 0.99, etc., and the values ​​of y and z can be 0.01, 0.02, 0.03, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1, etc., and of course, other values ​​within the above range can also be used, which are not limited here. When the total molar content of Ni, Co and N in the positive electrode material is within the above range, the positive electrode material has good electrochemical properties. It should be noted that the content of each element in the positive electrode material can be determined by instruments for qualitative analysis and / or quantitative analysis of each element known to the public, such as ICP, ICP-MS.

[0046] In some embodiments, the positive electrode material of the present application may be a nickel-cobalt-manganese-lithium ternary positive electrode material, or a nickel-cobalt-aluminum-lithium ternary positive electrode material.

[0047] In some embodiments, the M element includes at least one of Ti, Sb, Ta, Nb, W, Zr, Sr, and metal elements from Group IVB to Group VIB. An appropriate amount of doping can refine the grains of the positive electrode material, reduce the intensification of dislocation movement between grains caused by coarse grains, reduce the generation of cracks in the positive electrode material particles, and improve the structural stability of the positive electrode material.

[0048] In some embodiments, the particle strength of the positive electrode material is ≥0.28 MPa, and can be specifically 0.28 MPa, 0.29 MPa, 0.3 MPa, 0.31 MPa, 0.32 MPa, 0.35 MPa, 0.38 MPa, 0.39 MPa or 0.40 MPa, etc. Of course, it can also be other values ​​within the above range, which is not limited here.

[0049] In some embodiments, the specific surface area of ​​the positive electrode material is 0.3 m 2 / g~0.9m 2 / g, specifically 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g or 0.9m 2 / g, etc., and may of course be other values ​​within the above range, which are not limited here.

[0050] In some embodiments, the cathode material compaction density is ≥ 2.9 g / cm 3 , specifically 2.9g / cm 3 , 2.95g / cm 3 、3.0g / cm3 、3.1g / cm 3 、3.15g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.6g / cm 3 Of course, it can be other values ​​within the above range, which is not limited here. The compaction density of the positive electrode material is controlled within the above range, which is conducive to improving the energy density of the electrode sheet.

[0051] In some embodiments, the lithium ion diffusion coefficient of the positive electrode material is greater than 0.01 m 2 / s, specifically 0.01m 2 / s, 0.012m 2 / s, 0.013m 2 / s, 0.014m 2 / s, 0.015m 2 / s, 0.016m 2 / s, 0.018m 2 / s, 0.019m 2 / s, 0.021m 2 / s, 0.022m 2 / s or 0.025m 2 / s, etc., and of course, it can also be other values ​​within the above range, which is not limited here. Preferably, the lithium ion diffusion coefficient of the positive electrode material is ≥ 0.02m 2 / s

[0052] In some embodiments, the DC impedance of the positive electrode material is less than 0.01Ω, specifically 1.0*10 -3 , 1.0*10 -4 , 2.0*10 -4 , 3.0*10 -4 , 5.0*10 -4 、6.0*10 -4 ,7.0*10 -4 ,8.0*10 -4 ,9.0*10 -4 , 1.0*10 -5 , 2.0*10 -5 , 5.0*10 -5 ,8.0*10 -5 ,9.0*10 -5 The DC impedance of the positive electrode material is controlled within the above range, which shows that the interface impedance between the grains in the positive electrode material is controlled within a relatively low range, which is beneficial to the transmission and deintercalation of lithium ions and to improving the capacity of the positive electrode material.

[0053] In a second aspect, the present application provides a method for preparing a positive electrode material, such as Figure 1 As shown, the preparation method of the positive electrode material precursor includes the following steps:

[0054] S10: Preparing a precursor of a positive electrode material, wherein the precursor comprises a first precursor and a second precursor, the particle size D50 of the first precursor is 7 μm to 20 μm, and the particle size D50 of the second precursor is 2 μm to 6 μm; FWHM of the first precursor and the second precursor 101 Both are between 0.3 and 0.8, D 101 The crystal planes are all 10nm to 50nm.

[0055] S20: sintering the mixture of the precursor and the lithium salt to obtain a positive electrode material; wherein the particle size distribution width Span value of the lithium salt is less than 15, and the median particle size D50 of the lithium salt is less than 30 μm.

[0056] In the preparation method provided in the present application, the FWHM size of the positive electrode material after sintering is regulated by regulating the particle size distribution Span, D50 of the lithium salt and the crystal plane size of the precursor primary particle D101. By regulating the mass ratio of the first precursor and the second precursor and the median particle size of the lithium salt, the positive electrode material obtained by sintering can satisfy 0.001<(δ*span) / FWHM≤0.5, and the lithium ion transmission efficiency between the positive electrode material particles is improved by adjusting the particle size distribution width of the positive electrode material, thereby improving the energy density of the positive electrode material. At the same time, the powder conductivity is coordinated and controlled to improve the electronic conduction ability of the positive electrode material, and the discharge capacity of the positive electrode material is comprehensively improved, thereby improving the capacity loss caused by the small grain size. Therefore, the positive electrode material prepared by the preparation method of the present application can have high capacity, strong structural stability and cycle stability.

[0057] The preparation method of the present application is described in detail below with reference to the examples:

[0058] S10, preparing a precursor of a positive electrode material, wherein the precursor comprises a first precursor and a second precursor, the particle size D50 of the first precursor is 7 μm to 20 μm, and the particle size D50 of the second precursor is 2 μm to 6 μm; the FWHM of the first precursor and the second precursor 101 Both are between 0.3 and 0.8, D 101 The crystal planes are all 10nm to 50nm.

[0059] In some embodiments, the precursor is prepared by a co-precipitation process using nickel salt, cobalt salt and N salt.

[0060] In some embodiments, the precursor has the general chemical formula Ni x Co y N z(OH)2, wherein N is selected from Mn and / or Al, 0.80≤x<1, 0<y≤0.10, 0<z≤0.10. The N salt may be at least one of a manganese salt and an aluminum salt, i.e., a precursor of a nickel-cobalt ternary material.

[0061] In some embodiments, the nickel salt comprises at least one of nickel nitrate, nickel acetate, nickel chloride, and nickel sulfate. Preferably, the nickel source comprises nickel chloride.

[0062] In some embodiments, the cobalt salt comprises at least one of cobalt nitrate, cobalt acetate, cobalt chloride, and cobalt sulfate. Preferably, the cobalt salt comprises cobalt chloride.

[0063] In some embodiments, the N salt includes at least one of N nitrate, N acetate, N chloride, and N sulfate. Preferably, the N salt includes N chloride.

[0064] In some embodiments, the FWHM of the first precursor and the second precursor 101 They are all between 0.3 and 0.8, and specifically can be 0.3, 0.4, 0.5, 0.55, 0.58, 0.6, 0.65, 0.7 or 0.8, etc. Of course, they can also be other values ​​within the above range, which are not limited here.

[0065] In some embodiments, the D of the precursor 101 The crystal planes are all 10nm to 50nm, and can be 10nm, 12nm, 15nm, 20nm, 25nm, 28nm, 30nm, 35nm, 40nm, 45nm or 50nm, etc., and can also be other values ​​within the above range. Preferably, the D101 crystal plane of the precursor is 20nm to 50nm. It can be understood that the grain morphology of the primary particles of the precursor will affect the grain morphology of the primary particles of the positive electrode material. 101 When the D101 of the precursor is small, the larger the FWHM value, the smaller the FWHM value of the primary particles of the positive electrode material obtained after sintering, and the larger the grain size. Therefore, controlling the D101 of the precursor 101 Crystal size and FWHM 101 , the FWHM value of the sintered positive electrode material can be adjusted.

[0066] In some embodiments, the particle size D of the precursor 50 The particle size D of the precursor can be controlled by 50Within the above range, it is beneficial to control the particle size of the positive electrode material obtained by sintering, and further control the Span value of the positive electrode material.

[0067] S20: sintering the mixture of the precursor and the lithium salt to obtain a positive electrode material; wherein the particle size distribution width Span value of the lithium salt is less than 15, and the median particle size D50 of the lithium salt is less than 30 μm.

[0068] In some embodiments, the lithium salt includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, lithium sulfate, and lithium oxalate.

[0069] In some embodiments, the particle size distribution width Span value of the lithium salt is less than 15, and can be specifically 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 14.9, etc., and of course can be other values ​​within the above range, which are not limited here. Preferably, the particle size distribution width Span value of the lithium salt is 1.0 to 5.0. It can be understood that the particle size distribution width of the lithium salt is within the above range, and the particle size of the lithium salt is generally small. After the lithium salt and the precursor are fully fused, the growth of the primary particles of the precursor can be guaranteed, thereby regulating the size of the primary particles of the positive electrode material and the half-peak width of the positive electrode material within a suitable range.

[0070] In some embodiments, the median particle size D of the lithium salt is 50 <30 μm, specifically, it can be 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm or 29.9 μm, etc., and of course, it can also be other values ​​within the above range, which is not limited here. Preferably, the median particle size D of the lithium salt is 50 <8μm.

[0071] In some embodiments, the particle size D of the first precursor is 50 The particle size D of the second precursor is 7 μm to 20 μm. 50 The first precursor with larger particles is mixed with the second precursor with smaller particles. By adjusting the mass mixing ratio of the first precursor and the second precursor, the particle size Span value of the positive electrode material after sintering can be deeply controlled.

[0072] In some embodiments, the mass ratio of the first precursor to the second precursor is (1-20):1, specifically 1:1, 3:1, 5:1, 8:1, 10:1, 13:1, 15:1, 18:1 or 20:1, etc., and of course, it can be other values ​​within the above range, which is not limited here. Preferably, the mass ratio of the first precursor to the second precursor is (1-5):1.

[0073] In this application, by controlling the Span value and D 50, fully mixing the lithium salt with the precursor is beneficial to the particle size distribution width Span value, half maximum width (FWHM), and conductivity (δ) of the positive electrode material after sintering to be within the appropriate range, so that the electrochemical performance of the positive electrode material can reach the best state.

[0074] In some embodiments, the amount of lithium salt and precursor added satisfies: the ratio of the molar amount of Li to the total molar amount of metal in the precursor is (0.8-1.2):1; specifically, it can be 0.8:1, 0.9:1, 0.95:1, 1.0:1, 1.05:1, 1.09:1, 1.1:1, 1.15:1 or 1.2:1, etc., and of course, it can also be other values ​​within the above range, which are not limited here. Within this range, the degree of Li / Ni cation mixing can be reduced, and the excessive residual lithium on the surface of the sintered product can be prevented from affecting the processing performance and safety performance.

[0075] In some embodiments, the mixture of the cathode material precursor and the lithium source may be mixed by dry grinding, ball milling, etc., which is not limited here, as long as the components are mixed evenly.

[0076] In some embodiments, the mixing device may be at least one of a ball mill, a three-dimensional mixer, a high-speed mixer, and a VC mixer.

[0077] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere, wherein the oxygen content in the oxygen-containing atmosphere is ≥ 95%; the oxygen-containing atmosphere may be air or a mixed gas of air and oxygen.

[0078] In some embodiments, the temperature of the primary sintering treatment is 600°C to 1000°C; specifically, it can be 600°C, 700°C, 750°C, 800°C, 900°C, 950°C or 1000°C, etc., but it is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Within this range, sufficient air can promote the oxidation of divalent nickel to trivalent nickel, reduce the mixing of Li / Ni cations, and increase the capacity of lithium-rich manganese-based materials. At the same time, this temperature range is conducive to the formation of a layered structure without causing material decomposition.

[0079] In some embodiments, the time of a sintering treatment is 6 hours to 16 hours, and specifically may be 6 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 15 hours or 16 hours, etc., and of course may be other values ​​within the above range, which are not limited here.

[0080] In some embodiments, the mixture further includes a dopant containing a metal M element, wherein M includes at least one of Ti, Sb, Ta, Nb, W, Zr, Sr, and metal elements from Groups IVB to VIB.

[0081] In some embodiments, M may specifically be at least one of Al, Ti, Zr, Mg, Nb, W, Sb, Mo, Zr, Ti, Sr, B and Ba.

[0082] It can be understood that the dopant containing the metal M element can form LiMO2 with high lithium ion conductivity at the grain boundaries between the primary particles of the positive electrode material, which reduces the grain boundary transmission impedance and is beneficial to improving the rate performance of the positive electrode material.

[0083] In some embodiments, taking the mass of the precursor as 100%, the mass content of the M element in the positive electrode material is 0.1wt% to 0.5wt%, specifically 0.1wt%, 0.15wt%, 0.2wt%, 0.25wt%, 0.3wt%, 0.35wt%, 0.4wt%, 0.45wt% or 0.5wt%, and of course other values ​​within the above range may also be possible, which are not limited here.

[0084] Furthermore, in order to allow the dopant to better enter the lattice of the positive electrode material, the method further includes mixing the product of the primary sintering process with the dopant and performing a secondary sintering process;

[0085] In some embodiments, the temperature of the secondary sintering treatment is 600°C to 1000°C; specifically, it can be 600°C, 700°C, 750°C, 800°C, 900°C, 950°C or 1000°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0086] In some embodiments, the secondary sintering treatment time is 6 hours to 16 hours, and specifically may be 6 hours, 8 hours, 9 hours, 10 hours, 12 hours, 14 hours, 15 hours or 16 hours, etc., and of course may be other values ​​within the above range, which are not limited here.

[0087] In some embodiments, the solid phase mixing method can be dry grinding, ball milling, etc., which is not limited here, as long as the components are mixed evenly.

[0088] In some embodiments, the mixing device may be at least one of a ball mill, a three-dimensional mixer, a high-speed mixer, and a VC mixer.

[0089] In some embodiments, the secondary sintering process is performed in an oxygen-containing atmosphere, which may be air or a mixed gas of air and oxygen.

[0090] An embodiment of the present invention further provides a battery, Figure 4 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 4As shown, the battery includes a housing and an electrode assembly, and the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0091] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active layer 102 disposed on at least one surface of the positive electrode current collector 101 .

[0092] In some embodiments, the positive electrode current collector 101 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer 102 includes a positive electrode active material, which includes a compound that can reversibly embed and de-embed metal ions.

[0093] In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel.

[0094] In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O 4) 、LiNi 0.5 Mn 1.5 O4) or at least one of lithium iron phosphate (LiFePO4).

[0095] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.

[0096] In some embodiments, the negative electrode current collector 201 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 202 includes a negative electrode material, which is the negative electrode material of the first aspect described above or the negative electrode material prepared by the above preparation method. The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.

[0097] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.

[0098] Test method:

[0099] (1) Mastersizers 3000 was used to characterize the particle size volume distribution width of the material. The specific method is as follows:

[0100] The particle size volume distribution curve of the positive electrode material particles was measured by the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Co., Ltd., UK, according to the determination method of GB / T19077-2016. Span value = (D 90 -D 10 ) / D 50 (2) Testing method for specific surface area of ​​positive electrode materials:

[0101] The specific surface area of ​​the positive electrode material was tested using a Micromeritics Tristar 3020 specific surface area and pore size analyzer. A certain mass of powder was weighed and completely degassed under vacuum heating to remove the surface adsorbent. The specific surface area of ​​the particles was calculated using the nitrogen adsorption method based on the amount of nitrogen adsorbed. The unit is m 2 / g.

[0102] (3) Compacted density test of positive electrode materials:

[0103] The compaction density of the positive electrode material is tested using the American carver 4350, and the steps are as follows: weigh 1g of sample and put it into a mold and press it with a pressure of 3T for 30s. After pressing, the height is tested to calculate the compaction.

[0104] (4) XRD test of positive electrode materials:

[0105] The positive electrode material was characterized by using an XRD diffractometer (RIGAICU UITIMAIV), and the half-peak width of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material was obtained as FWHM.

[0106] (5) Particle strength test of positive electrode materials:

[0107] The particle strength of the positive electrode material particles was tested using a dynamic ultra-microhardness tester (DUH-211S) with reference to the standard "JIS R1639-5-2007 (compression strength)".

[0108] (6) Lithium ion diffusion test of positive electrode materials:

[0109] The electrode was made according to the negative electrode: carboxymethyl cellulose (2200): styrene-butadiene rubber (104A): carbon black SP: single-walled carbon nanotube = 95.77: 1.0: 2.0: 1.2: 0.03, and the compaction density was 1.65 g / cm 3 After assembling the button half-cell, the lithium ion diffusion coefficient was tested using the PITT method. The test temperature was 25°C and the test voltage range was 0.005-1.5V. (7) Conductivity test of the negative electrode.

[0110] (7) Powder conductivity test of positive electrode material:

[0111] Mettler FE38 was used to test the powder conductivity of the positive electrode material.

[0112] (8) DC impedance test of positive electrode material:

[0113] By giving a discharge current, pulsing for a few seconds, then standing still and then charging for a few seconds; according to the formula DCR = δV / I, the instantaneous voltage difference at the start and end is calculated.

[0114] (9) Electrochemical performance test:

[0115] The positive electrode material, conductive carbon and polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 93:5:2 to prepare a positive electrode slurry with a solid content of 50%, which is coated on aluminum foil and dried as a positive electrode sheet. A lithium sheet is used as a negative electrode sheet, and the electrolyte is sodium hexafluorophosphate-diethylene glycol dimethyl ether (NaPF6 concentration is 1 mol / L) to assemble into a button battery.

[0116] Power-off test

[0117] After standing for 12 hours, the battery test was carried out according to the following system: 0.1C charging and 0.1C discharging for 2 weeks (first effect), constant voltage cut-off current 0.005C; 0.5C charging and 0.5C discharging for 1 week (rate), constant voltage cut-off current 0.05C, 0.5C charging and 1C discharging for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charging and 2C discharging for 1 week (rate), constant voltage cut-off current 0.05C; 0.5C charging and 1C discharging for 50 weeks (cycles).

[0118] Example 1

[0119] (1) The first precursor (Ni 88 Co9Mn3(OH)2), D 50 = 15.0 μm, measured by XRD, the FWHM of the first precursor 101 is 0.52, D 101 Crystal plane size = 20.0 nm.

[0120] (2) The second precursor (Ni 88 Co9Mn3(OH)2), D 50 =3.0 μm, measured by XRD, the FWHM of the second precursor 101 is 0.49, D 101 Crystal plane size = 21 nm.

[0121] (3) Select lithium salt with a particle size distribution Span value of 4.0, D 50 =10.0μm.

[0122] (4) The lithium salt, the first precursor, the second precursor and the doping agent are fully mixed, wherein the first precursor: the second precursor = 7:3; the molar ratio of the lithium salt to the precursor metal (Me) is 1:1, that is, Li / Me = 1:1; the doping agent Nb2O5 is added at the same time, and the amount of Nb2O5 added is 0.1wt% of the total weight of the first precursor and the second precursor, and the mixture is fully mixed, and the mixture is placed in a sagger and placed in a box furnace for full sintering, with a heating rate of 2°C / min; the insulation temperature is 700°C, and the insulation time is 7h to obtain the positive electrode material.

[0123] The general chemical formula of the positive electrode material prepared in the present embodiment is LiNi 87.9 Co9Mn 2.9 Nb 0.2 O2

[0124] Example 2

[0125] The difference from Example 1 is:

[0126] (1) The first precursor (Ni 88 Co9Mn3(OH)2), D 50 = 20.0 μm, measured by XRD, the FWHM of the first precursor 101 is 0.52, D 101 Crystal plane size = 20.0 nm.

[0127] Example 3

[0128] The difference from Example 1 is:

[0129] (1) The first precursor (Ni 88 Co9Mn3(OH)2), D 50 =7.0 μm, measured by XRD, the FWHM of the first precursor 101 is 0.55, D 101 Crystal plane size = 20.0 nm.

[0130] Example 4

[0131] The difference from Example 1 is:

[0132] (1) The first precursor (Ni 88 Co9Mn3(OH)2), D 50 = 15.0 μm, measured by XRD, the FWHM of the first precursor 101 is 0.40, D 101 Crystal plane size = 30.0 nm.

[0133] (2) The second precursor (Ni 88 Co9Mn3(OH)2), D 50 =3.0 μm, measured by XRD, the FWHM of the second precursor 101 is 0.40, D 101 Crystal plane size = 30.0 nm.

[0134] (3) Select lithium salt with a particle size distribution Span value of 2.0, D 50 =5.0μm.

[0135] Example 5

[0136] The difference from Example 1 is:

[0137] (1) The first precursor (Ni 88 Co9Mn3(OH)2), D 50 = 15.0 μm, measured by XRD, the FWHM of the first precursor 101 is 0.65, D 101 Crystal plane size = 10.0 nm.

[0138] (2) The second precursor (Ni 88 Co9Mn3(OH)2), D 50 =3.0 μm, measured by XRD, the FWHM of the second precursor 101 is 0.65, D 101 Crystal plane size = 10.0 nm.

[0139] (3) Select lithium salt with a particle size distribution Span value of 15.0, D 50 =25.0μm.

[0140] Example 6

[0141] Different from Example 3, the preparation method further comprises:

[0142] (5) Based on the mass of the sintered product as 100wt%, 2wt% of graphene was added and mixed thoroughly. The mixture was placed in a sagger and sintered in a box furnace. The coating temperature was 600°C and the insulation time was 6h to obtain the coated positive electrode material.

[0143] Example 7

[0144] (1) The first precursor (Ni 88 Co9Mn3(OH)2), D 50 = 17.0 μm, measured by XRD, the FWHM of the first precursor 101 is 0.52, D 101 Crystal plane size = 25.0 nm.

[0145] (2) The second precursor (Ni 88 Co9Mn3(OH)2), D 50 =3.0 μm, measured by XRD, the FWHM of the second precursor 101 is 0.49, D 101 Crystal plane size = 21 nm.

[0146] (3) Select lithium salt with a particle size distribution Span value of 2.0, D 50 =5.0μm.

[0147] (4) The lithium salt, the first precursor and the doping agent are fully mixed, wherein the molar ratio of the lithium salt to the precursor metal (Me) is 1:1, that is, Li / Me=1:1; the doping agents ZrO2 and SrO2 are added at the same time, and the added amounts of ZrO2 and SrO2 are 0.1wt% and 0.1wt% of the weight of the first precursor, and the mixture is fully mixed, and the mixture is placed in a sagger and placed in a box furnace for full sintering, with a heating rate of 2°C / min; the insulation temperature is 700°C, and the insulation time is 7h to obtain a sintered product.

[0148] (5) Based on the mass of the sintered product as 100wt%, 3wt% of graphene was added and mixed thoroughly. The mixture was placed in a sagger and sintered in a box furnace. The coating temperature was 600°C and the insulation time was 6h to obtain the coated positive electrode material.

[0149] The general chemical formula of the positive electrode material prepared in the present embodiment is LiNi 87.9 Co9Mn 2.8 Zr 0.2 Sr 0.1 O2.

[0150] Example 8

[0151] The difference from Example 1 is:

[0152] (3) Select lithium salt with a particle size distribution Span value of 15.0, D 50 =25.0μm.

[0153] (4) The lithium salt, the first precursor, the second precursor and the doping agent are fully mixed, wherein the first precursor: the second precursor = 5:5; the molar ratio of the lithium salt to the precursor metal (Me) is 1:1, that is, Li / Me = 1:1; the doping agent Nb2O5 is added at the same time, and the amount of Nb2O5 added is 0.2wt% of the total weight of the first precursor and the second precursor, and the mixture is fully mixed, and the mixture is placed in a sagger and placed in a box furnace for full sintering, with a heating rate of 2°C / min; the insulation temperature is 700°C, and the insulation time is 7h to obtain the positive electrode material.

[0154] The general chemical formula of the positive electrode material prepared in the present embodiment is LiNi 87.8 Co9Mn 2.8 Nb 0.4 O2.

[0155] Example 9

[0156] The difference from Example 1 is:

[0157] (1) The first precursor (Ni 88 Co9Al3(OH)2), D 50 = 15.0 μm, measured by XRD, the FWHM of the first precursor 101 is 0.65, D 101 Crystal plane size = 17.5 nm.

[0158] (2) The second precursor (Ni 88 Co9 Al3(OH)2), D 50 =3.0 μm, measured by XRD, the FWHM of the second precursor 101 is 0.52, D 101 Crystal plane size = 19.0 nm.

[0159] The general chemical formula of the positive electrode material prepared in the present embodiment is LiNi 87.9 Co9A 2.9 Nb 0.2 O2.

[0160] Comparative Example 1

[0161] (1) The first precursor (Ni 88 Co9Mn3(OH)2), D 50 = 15.0 μm, measured by XRD, the FWHM of the first precursor101 is 0.50, D 101 Crystal plane size = 21.0 nm.

[0162] (2) Select lithium salt with a particle size distribution Span value of 4.0, D 50 =10.0μm.

[0163] (3) The lithium salt, the first precursor and the doping agent are fully mixed, wherein the molar ratio of the lithium salt to the precursor metal (Me) is 1:1, that is, Li / Me=1:1; the doping agent Nb2O5 is added at the same time, and the amount of Nb2O5 added is 0.1wt% of the total weight of the first precursor, and the mixture is fully mixed, and the mixture is placed in a sagger and placed in a box furnace for full sintering, with a heating rate of 2°C / min; the insulation temperature is 700°C, and the insulation time is 7h to obtain the positive electrode material.

[0164] Comparative Example 2

[0165] (1) The first precursor (Ni 88 Co9Mn3(OH)2), D 50 =5.0μm, measured by XRD, the FWHM of the first precursor 101 is 0.49, D 101 Crystal plane size = 21.0 nm.

[0166] (2) Select lithium salt with a particle size distribution Span value of 4.0, D 50 =10.0μm.

[0167] (3) The lithium salt, the first precursor and the doping agent are fully mixed, wherein the molar ratio of the lithium salt to the precursor metal (Me) is 1:1, that is, Li / Me=1:1; the doping agent Nb2O5 is added at the same time, and the amount of Nb2O5 added is 0.1wt% of the total weight of the first precursor, and the mixture is fully mixed, and the mixture is placed in a sagger and placed in a box furnace for full sintering, with a heating rate of 2°C / min; the insulation temperature is 700°C, and the insulation time is 7h to obtain the positive electrode material.

[0168] Table 1. Comparison of process parameters of embodiments and comparative examples

[0169]

[0170] Table 2. Test data of positive electrode materials prepared in Examples and Comparative Examples

[0171]

[0172]

[0173] According to the test data of Example 1 and Example 2, Example 2 increases the particle size D of the first precursor. 50 , reducing the δ conductivity of the cathode material after sintering, δ*Span / FWHM 003 As the ratio decreases, the capacity of the positive electrode material decreases, but the cycle retention rate improves.

[0174] According to the test data of Example 1 and Example 3, Example 3 reduces the particle size D of the first precursor. 50 , which improves the δ conductivity of the cathode material after sintering, δ*Span / FWHM 003 As the ratio increases, the discharge capacity of the positive electrode material increases, but the cycle performance decreases slightly.

[0175] According to the test data of Example 1 and Example 4, Example 4 increases the 101 crystal plane size of the first precursor and the second precursor on the basis of Example 1, and reduces the D 50 and Span value, so that the lithium salt reacts fully with the precursor during the sintering process, reducing the FWHM of the positive electrode material after sintering 003 , δ*Span / FWHM 003 The ratio is improved, the grain size of the positive electrode material is increased, the number of grain boundaries between the grains is reduced, the lithium ion transmission efficiency within the positive electrode material particles is improved, the grain size of the positive electrode material is increased, and the capacity of the positive electrode material is improved compared with Example 1, but the cycle performance of the positive electrode material is slightly reduced. This is because the unit cell shrinks more severely during the charge and discharge process, and the structural stability of the positive electrode material is slightly reduced.

[0176] According to the test data of Example 1 and Example 5, Example 5 reduces the 101 crystal plane size of the first precursor and the second precursor on the basis of Example 1, and increases the D 50 and Span value, which improves the FWHM of the cathode material after sintering 003 , δ*Span / FWHM 003 As the ratio decreases, the grain size of the positive electrode material becomes smaller, the number of grain boundaries between the grains increases, the lithium ion transmission efficiency within the positive electrode material particles decreases, and the capacity of the positive electrode material is slightly lower than that in Example 1. However, the structural stability of the positive electrode material increases, the cycle performance of the positive electrode material is improved, and the interface impedance of the positive electrode material also increases slightly.

[0177] According to the test data of Example 1 and Example 6, Example 6 reduces the particle size D of the first precursor on the basis of Example 1. 50 , resulting in a slight decrease in the Span value of the positive electrode material after sintering, but at the same time, graphene coating in the material greatly improved the δ conductivity of the positive electrode material, δ*Span / FWHM 003As the ratio increases, the discharge capacity of the positive electrode material increases, but the cycle performance decreases slightly.

[0178] According to the test data of Example 1 and Example 7, Example 7 increases the particle size D of the first precursor based on Example 1. 50 , while reducing the particle size D50 and span of the lithium salt, so that the lithium salt fully reacts with the precursor during the sintering process, reducing the FWHM of the positive electrode material after sintering 003 At the same time, the use of graphene coating improves the δ conductivity, the δ*Span / FWHM003 ratio, and the discharge capacity of the positive electrode material, but the cycle performance decreases slightly.

[0179] According to the test data of Example 1 and Example 8, Example 8 adjusts the mass ratio of the first precursor to the second precursor and the particle size distribution of the added lithium salt on the basis of Example 1, and the particle size distribution width of the lithium salt is increased, thereby improving the FWHM of the positive electrode material after sintering. 003 And the particle size distribution Span of the positive electrode material, δ*Span / FWHM 003 As the ratio increases, the grain size of the positive electrode material becomes smaller, the number of grain boundaries between the grains increases, the lithium ion transmission efficiency within the positive electrode material particles decreases, and the capacity of the positive electrode material decreases slightly compared to Example 1. Due to the increase in the particle size distribution width of the positive electrode material, the cycle performance of the positive electrode material also decreases slightly.

[0180] Example 9 is a nickel-cobalt-aluminum based positive electrode material, in which the (δ*span) / FWHM of the positive electrode material is controlled within a suitable range, and the positive electrode material can have high capacity, strong structural stability and cycle stability.

[0181] In the comparative examples, comparative example 1 only used D 50 =15μm The precursor produced by continuous method has a wide particle size distribution. The compaction density of the positive electrode material after sintering is low, resulting in a serious small δ of the positive electrode material and a slightly larger Span value. δ*Span / FWHM 003 The ratio is too small, the capacity of the positive electrode material is low, and the cycle is poor.

[0182] In the preparation process of Comparative Example 2, only the precursor produced by the continuous method with D50=5 μm was used. Due to the small particle size of the precursor, the positive electrode material D after sintering 50 Smaller, resulting in a larger specific surface area of ​​the cathode material, while the particle strength is slightly worse, although it leads to δ*Span / FWHM 003 The ratio is high, but its capacity and cycle performance are not ideal.

[0183] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A positive electrode material, It is characterized in that The positive electrode material is a nickel-cobalt-lithium composite oxide, and the powder conductivity of the positive electrode material is δS / cm 2 , the particle size distribution width of the positive electrode material is Span, in the XRD spectrum of the positive electrode material, the half-peak width of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material is FWHM, and the positive electrode material satisfies: 0.001<(δ*span) / FWHM≤0.

5.

2. The positive electrode material according to claim 1, It is characterized in that It meets at least one of the following technical features: (1) The particle size volume distribution width of the positive electrode material satisfies: 0.9≤Span≤1.5; (2) 0.15 ≤ FWHM ≤ 0.19; (3) The powder conductivity of the positive electrode material is δS / cm 2 , 0.005≤δ≤0.

08.

3. The positive electrode material according to claim 1, It is characterized in that 0.01<(δ*span) / FWHM≤0.

24.

4. The positive electrode material according to claim 1 or 2, It is characterized in that The particle size of the positive electrode material satisfies: 1.0 μm<D 10 <7.0μm,8.0μm<D 50 <20.0μm, 15.0μm<D 90 <30.0μm.

5. The positive electrode material according to claim 1 or 2, It is characterized in that It meets at least one of the following technical features: (1) The particle strength of the positive electrode material is ≥ 0.28Mpa; (2) The compaction density of the positive electrode material is ≥ 2.9 g / cm 3 ; (3) The specific surface area of ​​the positive electrode material is 0.3 m 2 / g~0.9m 2 / g.

6. The positive electrode material according to claim 1, It is characterized in that The lithium ion diffusion coefficient of the positive electrode material is greater than 0.01 m 2 / s.

7. The positive electrode material according to claim 1, It is characterized in that The chemical formula of the positive electrode material is Li a Ni x Co y N z M w O 2 , wherein 0.75≤a≤1.05, 0.80≤x<1, 0<y≤0.10, 0<z≤0.10, 0<w≤1-xyz, N is Mn or Al, and M is a doping element.

8. The positive electrode material according to claim 6, It is characterized in that The M element includes at least one of Ti, Sb, Ta, Nb, W, Zr, Sr, and metal elements of Groups IVB to VIB.

9. The positive electrode material according to claim 6, It is characterized in that The direct current impedance of the positive electrode material is less than 0.01Ω.

10. A battery, It is characterized in that The battery comprises the positive electrode material according to any one of claims 1 to 9.